Networking Abroad: A Process Model of How Expatriates Form Support Ties to Facilitate Adjustment - Farh, Crystal I. C.; Bartol, Kathryn M.; Shapiro, Debra L.; Shin, Jiseon (Academy of Management Review, 2010)
In order to adjust, expatriates working abroad must form network ties in the host country to obtain critical informational and emotional support resources. We present a five-stage process model that delineates how expatriates form adjustment-facilitating support ties in a culturally unfamiliar context. We then provide propositions about how the progression of each stage is influenced by various expatriate-, actor-, and context-related factors. We conclude by discussing our model's implications for future research and managerial action.